PEMBENTUKAN PROGRAM LEGISLASI NASIONAL BERLANDASKAN PANCASILA - Sofian, Sofian; Riskiyono, Joko (Faculty of Law, Tanjungpura University, 2019)
Abstract The national legislation program makes Pancasila the source of all sources of law and as the basis of the state based on the philosophy and values of Pancasila animates and influences the process of legislation formation. In the research, the author using normative legal research method. But the fact that legislation generated through the process of formulating legislation has not provided a guarantee of justice and welfare for the people, so that the resulting law is still far from the goal of realizing prosperity for all Indonesian people. Abstrak Program legislasi nasional menjadikan Pancasila sebagai sumber dari segala sumber hukum dan sebagai dasar negara yang berpedoman Pada falsafah dan nilai-nilai pancasila menjiwai dan mempengaruhi proses pembentukan legislasi. Di dalam penelitian ini menggunakan metode penelitian hukum normatif. Hasil penelitian ini menunjukkan bahwa kenyataannya legislasi yang dihasilkan melalui proses pembentukan peraturan perundang-undangan belum memberikan jaminan keadilan dan kesejahteraan bagi rakyat, sehingga undang-undang yang dihasilkan masih jauh dari cita-cita yaitu mewujudkan kesejahteraan bagi seluruh rakyat indonesia.